La araucana: autosacramental de Lope Félix de Vega Carpio - Vega Carpio, Lope Félix de; Medina, José Toribio (Anales de la Universidad de Chile, 1915)
Incluye prólogo "La historia de América, fuente del antigüo teatro español" de J. T. Medina.